Alexander von Humboldt and planet earth’s green mantle - Anne Buttimer (Unité Mixte de Recherche 8504 Géographie-cités, 2012)
This paper opens with a summary overview on the career journey of the pioneer geographer, Alexander von Humboldt (1769-1859), the scholarly and political contexts where his work unfolded and his associations with contemporary colleagues. Then follows an English translation of his Essai sur la géographie des plantes (1805), a work which could be regarded as epitome of his overall world-view. A concluding chapter explores some “geo-poetic” elements which afford essential clues to Humboldt’s success in bridging the worlds of scientific and humanist knowledge.